KISTA DENTIGEROUS PADA RAMUS MANDIBULA KANAN (Laporan Kasus) - Rina Simamora; Tis Karasutisna; Alwin Kasim (Faculty of Dentistry, Universitas Indonesia, 2015)
A male was 55 years old, came to Oral Surgery Department-Hasan Sadikin Hospital Bandung. He had complaining of the swelling on the right side of mandible and since 1 month ago. He has got the fistula with puss on the ramus region. From the clinical feature and radiologically finding the diagnostic was Dentigerous Cyst ed causa impacted teeth 48 and was treated by extirpation-biopsy by extra oral approach for removal the cyst and the impacted of teeth 48 in general anesthesia. After 3 months investigation it shown there was no recurrencies of the cyst and the patient has not complaint.